2000
DOI: 10.2214/ajr.175.5.1751381
|View full text |Cite
|
Sign up to set email alerts
|

Helical CT Angiography and Three-Dimensional Reconstruction of Total Anomalous Pulmonary Venous Connections in Neonates and Infants

Abstract: The combination of axial and 3D images in helical CT angiography is helpful in the assessment of a total anomalous pulmonary venous connection containing the individual pulmonary vein, and this combination can be a good diagnostic tool in preoperative evaluation of neonates and infants with a total anomalous pulmonary venous connection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(53 citation statements)
references
References 14 publications
2
50
0
1
Order By: Relevance
“…Computerized tomography (CT) and magnetic resonance imaging are being used more recently in diagnosing and evaluating CHD. [2][3][4][5] In neonates with suspected CHD, CT may be used instead of catheterization to obtain detailed anatomic evaluation of the heart and great vessels if echocardiography is not conclusive. We report two cases where the diagnosis of TAPVR was not confirmed by echocardiography.…”
Section: Introductionmentioning
confidence: 99%
“…Computerized tomography (CT) and magnetic resonance imaging are being used more recently in diagnosing and evaluating CHD. [2][3][4][5] In neonates with suspected CHD, CT may be used instead of catheterization to obtain detailed anatomic evaluation of the heart and great vessels if echocardiography is not conclusive. We report two cases where the diagnosis of TAPVR was not confirmed by echocardiography.…”
Section: Introductionmentioning
confidence: 99%
“…15 Although conventional catheter angiography has been accepted as the gold standard-and it does enable detailed evaluation of the drainage of the PVs and of possible obstructions-it carries the risk of cardiac arrest and even of death in cases of obstructive TAPVC and severe cyanosis. 16 Magnetic resonance imaging offers several advantages over cardiovascular imaging: its true multiplanar capabilities, its lack of ionizing radiation, its absence of need for an iodinated contrast agent, and its ability not only to characterize shunt direction but also to quantify flow. [17][18][19] However, its disadvantages include lower spatial resolution, increased pixel size, susceptibility artifacts, and longer examination times.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al [9], studying 14 patients with TAPVC demonstrated that the combination of MDCT with three dimensional reconstruction helped in the diagnosis of TAPVC, being a good tool in the preoperative evaluation of neonates and infants [9]. However, it is not sufficiently adequate for visualization of intracardiac structures, due to heart rate and respiratory movements generally high.…”
Section: Discussionmentioning
confidence: 99%
“…But recently, magnetic resonance imaging and multidetector computed tomography (MDCT) have been employed with greater emphasis on congenital heart disease to replace the invasive procedure [8][9][10].…”
Section: Introductionmentioning
confidence: 99%